Critical appraisal of inflammatory markers in cardiovascular risk stratification. (October 2014) - Krintus, Magdalena; Kozinski, Marek; Kubica, Jacek; Sypniewska, Grazyna
Abstract Despite great progress in prevention strategies, pharmacotherapy and interventional treatment of coronary artery disease (CAD), cardiovascular events still constitute the leading cause of mortality and morbidity in the modern world. Traditional risk factors, including hypertension, diabetes mellitus, smoking, obesity, dyslipidemia, and positive family history account for the occurrence of the majority of these events, but not all of them. Adequate risk assessment remains the most challenging in individuals classified into low or intermediate risk categories. Inflammation plays a key role in the initiation and promotion of atherosclerosis and may lead to acute coronary syndrome (ACS) by the induction of plaque instability. For this reason, numerous inflammatory markers have been extensively investigated as potential candidates for the enhancement of cardiovascular risk assessment. This review aims to critically assess the clinical utility of well-established (C-reactive protein [CRP] and fibrinogen), newer (lipoprotein-associated phospholipase A2 [Lp-PLA2] and myeloperoxidase [MPO]) and novel (growth differentiation factor-15 [GDF-15]) inflammatory markers which, reflect different pathophysiological pathways underlying CAD. Although according to the traditional approach all discussed inflammatory markers were shown to be associated with the risk of future cardiovascular events in individuals with and without CAD, their clear clinical utility remains not fully elucidated. Current recommendations of numerous scientific societies predominantly advocate routine assessment of CRP in healthy people with intermediate cardiovascular risk. However, these recommendations substantially vary in their strength among particular societies. These discrepancies have a multifactorial background, including: (i) the strong prognostic value of CRP supported by solid scientific evidence and proven to be comparable in magnitude with that of total and high-density lipoprotein cholesterol, or hypertension, (ii) favourable analytical characteristics of commercially available CRP assays, (iii) lack of CRP specificity and causal relationship between CRP concentration and cardiovascular risk, and (iv) CRP dependence on other classical risk factors. Of major importance, CRP measurement in healthy men ≥50 years of age or healthy women ≥60 years of age with low-density lipoprotein cholesterol <130 mg/dL may be helpful in the selection of patients for statin therapy. Additionally, evaluation of CRP and fibrinogen or Lp-PLA2 may be considered to facilitate risk stratification in ACS patients and in healthy individuals with intermediate cardiovascular risk, respectively. Nevertheless, the clinical utility of CRP requires further investigation in a broad spectrum of CAD patients, while other promising inflammatory markers, particularly GDF-15 and Lp-PLA2, should be tested in individuals both with and without established CAD. Further studies should also focus on novel performance metrics such as measures of discrimination, calibration and reclassification, in order to better address the clinical utility of investigated biomarkers and to avoid misleadingly optimistic results. It also has to be emphasized that, due to the multifactorial pathogenesis of CAD, detailed risk stratification remains a complex process also involving, beyond assessment of inflammatory biomarkers, the patient's clinical characteristics, results of imaging examinations, electrocardiographic findings and other laboratory parameters (e.g. lipid profile, indices of renal function, markers of left ventricular overload and fibrosis, and biomarkers of myocardial necrosis, preferably cardiac troponins).